Stage V Chronic Kidney Disease on Hemodialysis and Hypertensive Emergency: A Case Report and Literature Review - Edi Saputra; Rista Silvana; Indri Ramayanti; Mutiara Malihah Putri; Muhammad Saleh Ramadhan; Anisatul Aflah (Universitas Muhammadiyah Palembang, 2026)
ABSTRACT Hypertension and chronic kidney disease have a bidirectional relationship in which uncontrolled hypertension accelerates kidney damage, whereas declining kidney function worsens hypertension through fluid retention, activation of the renin–angiotensin–aldosterone system, increased sympathetic activity, and endothelial dysfunction. In advanced stages, this interaction may progress to hypertensive emergency with acute target organ damage. This case report describes a 40-year-old woman with stage V chronic kidney disease on hemodialysis who presented with dyspnea, severe headache, nausea, and decreased appetite. Her blood pressure on admission was 193/103 mmHg, accompanied by bilateral fine crackles and signs of anemia. Laboratory examination revealed hemoglobin 6.9 g/dL, urea 80 mg/dL, creatinine 6.2 mg/dL, and an estimated glomerular filtration rate of 9.85 mL/min/1.73 m². Chest radiography showed cardiomegaly and early pulmonary congestion, while electrocardiography showed no acute abnormality. The patient was diagnosed with hypertensive emergency in stage V chronic kidney disease on hemodialysis, accompanied by fluid overload and severe anemia. Management consisted of titrated intravenous nicardipine, correction of volume overload with hemodialysis, and packed red cell transfusion for symptomatic severe anemia. After stabilization, oral antihypertensive agents consisting of amlodipine, candesartan, and clonidine were administered. This case highlights the importance of distinguishing hypertensive emergency from severe hypertension in advanced chronic kidney disease, because this classification determines the need for intravenous therapy, close monitoring, and comprehensive management of associated complications.Keywords: anemia, chronic kidney disease, hemodialysis, hypertensive emergency